A note on a very recent paper "Feedback control for nonlinear evolutionary equations with applications". (August 2023) - Yin, Bin; Zeng, Biao
Abstract: In this note we correct and improve the proofs of the main lemmas in a very recent publication (Zeng, 2022), in which the hypotheses of boundedness, coerciveness and relaxed monotonicity for the operators are considered.